Hardware implementation of a real‐time adaptive single‐phase auto‐reclosure for power transmission lines. (13th February 2020) - Jannati, Mohsen; Moshtagh, Jamal
Summary: In order to distinguish permanent single line‐to‐ground faults from transient faults and prevent reclosing in the case of a permanent fault occurrence, an adaptive algorithm is proposed. The proposed algorithm prevents unsuccessful reclosing if the event is transient by identifying the extinguishing time of the secondary arc, thus preventing long interruptions in the electricity production. Furthermore, an adaptive auto‐reclosure is constructed based on the proposed algorithm. Extensive simulations in the EMTP environment and performing tests by the constructed reclosure and a test relay device (Vebko) using practical data verify the speed and accuracy of the proposed algorithm.